(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Memory studies as a multidisciplinary study area combine intellectual strands from many domains. It examines the forms and functions of representing the past. Life narratives contribute to the study of autobiographical memory studies. Transgenders of India fought for decades with the society and governments to establish their status as the Third Gender. They were the detested lot of the county, deprived of basic human rights and provisions and removed from mainstream society in all possible ways.